Analyzing the mechanisms involved in the antidiabetic activity of some native plants - Dehury, Lorie; Mahapatra, Satyapriya; Gauda, Anshuman; Maharana, Laxmidhar; Panigrahi, Ghanshyam (Journal of Applied Pharmaceutical Research, 2024)
Background: Research on diabetes treatment is advancing yearly, and it is estimated that 643 million adults worldwide will have diabetes by 2030. This is a comprehensive review of antidiabetic mechanisms in medicinal plants, aims to identify natural antidiabetic plants and provide details on their mechanisms of action, and rigorous testing techniques. Methodology: Information was gathered from offline and online sources to identify indigenous medicinal plants that lower blood glucose. Different databases were searched for ethnopharmacological literature using the following keywords: medicinal plants, diabetes, and India. Other sections about clinical trials, toxicological evaluations of certain plants, and preclinical trials have since been added. These sections were retrieved from Scopus using pertinent keywords. In this study, 117 species of medicinal plants from 55 families that are used to treat diabetes mellitus were listed. Conclusion: The variety of plants discussed in this review clearly demonstrated the importance of herbal plants in the treatment of diabetes. Result of the study shows Fabaceae, Rutaceae, and Combretaceae were the most prevalent plant families and species having antidiabetic properties among these plants. It also gives researchers information that they may use to develop future plans, like finding plants that may be effective in preventing diabetes and isolating bioactive molecules to help manage the disease. More research is necessary to completely comprehend these newly identified anti-diabetic drugs at the molecular, therapeutic, and physiological levels, nevertheless, in order to treat and manage diabetes mellitus globally